A design approach to mathematics teacher educator development in East Africa - Golding, Jennie; Batiibwe, Marjorie Sarah K. (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2021)
Mathematical functioning in sub-Saharan Africa remains persistently weak in global terms. This limits the flourishing of young people and communities in the region. Moreover, affordable, effective ways to address the issue are not well established. This paper analyses outcomes from a blended learning ‘Mathematical Thinking and IT’ course, iteratively adapted for East African primary mathematics teacher educators. The course adopted theoretical approaches derived from the mathematics, teacher and technology education literatures. It aimed to address the problem of low mathematical functioning by equipping participants for their own work, and also for supporting local collaborative teacher development workshops. The reported study asked, ‘What are the affordances and constraints of the adapted course and the available technology for mathematics teacher educator development in this context?’A variety of qualitative tools were used to track the course’s impact on the ten mathematics teacher educator participants over six months, as they attempted to transfer course learning to their home professional context. The analysis adopted an ethnographic lens. Outcomes suggested participants with a broad mathematical and pedagogical capacity for change, including critical levels of reflection, made significant progress in their technological, mathematical and mathematics pedagogical expertise. However, teacher educators without such a threshold capacity appeared not able to re-envision practice. Free subjectspecific software was appreciated by all participants, but not yet reliably accessible in these teacher educators’ institutional contexts. The reported study evidences the potential for affordable, sustainable, development of many mathematics teacher educators in this context, but further research is needed. Similar courses should take account of local technological and education constraints.